Islamic or universal human rights? The OIC's independent permanent human rights commission - Marie Juul Petersen (Danish Institute for International Studies (DIIS), 2012)
In June 2011 the Organisation of Islamic Cooperation established the Independent Permanent Human Rights Commission, with the objective to advance human rights and support the Member States' efforts to consolidate civil, political, economic, social and cultural rights. This report provides an introduction to the new human rights commission, presenting the background to its establishment, its objectives, activities and experts, as well as its relation to the international human rights community and its conception of human rights. The report concludes by discussing some of the potentially problematic aspects of the Commission, as well as some of its strengths, seen from a Danish perspective.
Keywords: 300